The essential guide to family & medical leave - Guerin, Lisa, 1964- (Nolo, 2024)
"The federal Family and Medical Leave Act (FMLA) helps employees balance the demands of work and family. But the law can be hard for employers to apply in the real world-especially when it comes to tracking intermittent leave, completing the proper paperwork, and determining eligibility for different types of leave. This book has the answers-in plain English-to every employer's tough questions about the FMLA. It provides detailed information, sample forms, and tools that will help employers figure out who is eligible for leave, what types of leave are covered, how much leave employees may take, and how to comply with notice and other paperwork requirements"--